Signifikansi Literasi Al-Quran Dalam Memproteksi Radikalisme Tafsir - Moh Akib (Fakultas Ushuluddin dan Komunikasi Islam, 2024)
Al-Quran literacy play a very important role in preventing exegetical radicalism in society. The aim of this article is to explore how a deeper understanding of the Koran can be a solution to overcome the increasing threat of radicalism. This article highlights that interpretive radicalism is often the result of a shallow understanding of the Al-Quran text. This is due to a lack of in-depth understanding of the historical, cultural and social context. Therefore, education that leads to good Al-Qur'an literacy can be the most important defense in overcoming weaknesses and potential different understandings. You will not only understand the scriptures literally, but also the context, purpose, and wisdom behind each passage. This approach helps individuals develop a more enlightened understanding and be open to different interpretations. Second, this article highlights the importance of Qur'anic education and reading and writing not only for scholars and religious scholars, but also for ordinary people. Comprehensive and affordable Al-Quran education helps raise society's collective awareness and enables each individual to wisely filter evolving information and interpretations. At the end of the article, he concludes that education and knowledge of the Koran play an important role in preventing exegetical radicalism. A deep and holistic understanding of the Koran should make society more resistant to the influence of extremism and radicalism which can damage societal peace and harmony.